Hypertonic Saline in Human Sepsis: A Systematic Review of Randomized Controlled Trials. (June 2019) - Orbegozo, Diego; Vincent, Jean-Louis; Creteur, Jacques; Su, Fuhong
Abstract : The role of hypertonic saline in sepsis remains unclear because clinical data are limited and the balance between beneficial and adverse effects is not well defined. In this systematic literature review, we searched PubMed and Embase to identify all randomized controlled trials up until January 31, 2018 in which hypertonic saline solutions of any concentration were used in patients of all ages with sepsis and compared to a cohort of patients receiving an isotonic fluid. We identified 8 randomized controlled trials with 381 patients who had received hypertonic saline. Lower volumes of hypertonic saline than of isotonic solutions were needed to achieve the desired hemodynamic goals (standardized mean difference, −0.702; 95% CI, −1.066 to −0.337; P < .001; moderate-quality evidence). Hypertonic saline administration was associated with a transient increase in sodium and chloride concentrations without adverse effects on renal function (moderate-quality evidence). Some data suggested a beneficial effect of hypertonic saline solutions on some hemodynamic parameters and the immunomodulatory profile (very low–quality evidence). Mortality rates were not significantly different with hypertonic saline than with other fluids (odds ratio, 0.946; 95% CI, 0.688–1.301; P = .733; low-quality evidence). In conclusion, in our meta-analysis of studies in patients with sepsis, hypertonic saline reduced the volume of fluid needed to achieve the same hemodynamic targets but did not affect survival.